Methods of the National Nutrition Survey 1999 Metodología de la Encuesta Nacional de Nutrición 1999 - Elsa Resano-Pérez; Ignacio Méndez-Ramírez; Teresa Shamah-Levy; Juan A Rivera; Jaime Sepúlveda-Amor (Salud Pública de México, 2003)
OBJECTIVE: To describe the methods and analyses of the 1999 National Nutrition Survey (NNS-99). MATERIAL AND METHODS: The 1999 National Nutrition Survey (NNS-99) is a probabilistic survey with nationwide representativity. The NNS-99 included four regions and urban and rural areas of Mexico. The last sampling units were households, selected through stratified cluster sampling. The study population consisted of children under five years of age, school-age children (6-11 years), and women of childbearing age (12-49 years). Data were collected on anthropometric measurements, hemoglobin levels, morbidity and its determinants, and socioeconomic and demographic characteristics. In addition, data on diet and micronutrients intakes (iron, zinc, vitamin A, folic acid, vitamin C, and iodine) were obtained in a sub-sample of subjects. RESULTS: The response rate for the NNS-99 was 82.3%; the non-response rate was 5.9% and the remaining did not participate due to uninhabited houses. CONCLUSIONS: This survey updates the information on nutritional status in Mexico and should serve as the basis for food and nutrition policy-making and priority program design. OBJETIVO: Describir la metodología y análisis de la Encuesta Nacional de Nutrición 1999 (ENN-99). MATERIAL Y MÉTODOS: La ENN-99 es probabilística, con representatividad nacional de cuatro regiones y estratos urbano/rural. Las unidades últimas de muestras son los hogares seleccionados por muestreo estratificado y por conglomerados. La población de estudio fueron los niños menores de cinco años de edad, los niños 6-11 años (escolares) y las mujeres de 12-49 años, en quienes se obtuvieron mediciones antropométricas, niveles de hemoglobina, información sobre morbilidad y sus determinantes, datos socieconómicos y demográficos, y en una submuestra se determinaron micronutrimentos (hierro, zinc, vitamina A, ácido fólico, vitamina C, yoduria) y se obtuvo información sobre dieta. RESULTADOS: La Encuesta obtuvo una tasa de respuesta de 82.3%, la no respuesta se asoció en 5.9% a no respuesta del informante y el resto fue ocasionado por no estar habitadas las viviendas seleccionadas. CONCLUSIONES: La información obtenida a través de esta encuesta actualiza la información existente en nuestro país y es la base para la formulación de políticas y programas prioritarios.